Sugammadex-Associated Hypotension, Bradycardia, Asystole, and Death - Kazim Mirza; Kathryn Landoski; Dilip Thakar; Jagtar Heir-Singh; Timothy Jackson; Cynthia Kassab (Case Reports in Anesthesiology)
On December 16, 2015, the Food and Drug Administration (FDA) in the United States approved sugammadex (Bridion, Merck and Co), a modified gamma-cyclodextrin, to be used as a reversal agent. It is a first and unique selective nondepolarizing steroidal muscle relaxant (NDSMR) binding agent with a great affinity for rocuronium and vecuronium. However, there have been several recently published case reports of bradycardia and asystole immediately after sugammadex administration for the reversal. This report presents a case of sugammadex administration followed by rapidly progressing bradycardia leading to asystole and subsequent death. The family has provided the written consent to share this case report.